pH-Dependent Optical Properties of Synthetic Fluorescent Imidazoles - Berezin, Mikhail Y. (2009)
An imidazole moiety is often found as an integral part of fluorophores in a variety of fluorescent proteins and many such proteins possess pH dependent light emission. In contrast, synthetic fluorescent compounds with incorporated imidazoles are rare and have not been studied as pH probes. In this report, the richness of imidazole optical properties, including pH sensitivity, was demonstrated via a novel imidazole-based fluorophore 1H-imidazol-5-yl-vinyl-benz[e]indolium. Three species corresponding to protonated, neutral and deprotonated imidazoles were identified in the broad range of pH 1-12. The absorption and emission bands of each species were assigned by comparative spectral analysis with synthesized mono- and di-N-methylated fluorescent imidazole analogues. pKa analysis in the ground and the excited states showed photoacidic properties of the fluorescent imidazoles due to the excited state proton transfer (ESPT). This effect was negligible for substituted imidazoles. The assessment of a pH sensitive center in the imidazole ring revealed the switching of the pH sensitive centers from 1-N in the ground state to 3-N in the excited state. The effect was attributed to the unique kind of the excited state charge transfer (ESCT) resulting in a positive charge swapping between two nitrogens.